2021
DOI: 10.9734/mrji/2021/v31i130298
|View full text |Cite
|
Sign up to set email alerts
|

murA, uhpT, glpT and fosA Genes of Fosfomycin Resistance in Multi-drug Resistant E. coli Isolated from Hematological Malignancies' Patients with Blood Stream Infection

Abstract: Aim: To estimate the prevalence of murA, uhpT, glpT and fosA resistance genes of fosfomycin in multidrug resistant Escherichia coli isolated from patients suffering from hematological malignancies with on top blood stream infection together with correlating this distribution to the rate of expression of AmpC, ESBLs and MBLs in such isolates. Methods: 205 blood samples collected from patients with underlying hematological malignancies were cultured to isolate E. coli strains. Multidrug resistance was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…It has been observed that FosA gene was found in seven types of E. coli pathogenic strains, which controls the metabolization of fosfomycine via regulating expression of metal-dependent glutathione transferase . It is known that the Klebsiella pneumoniae and P.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that FosA gene was found in seven types of E. coli pathogenic strains, which controls the metabolization of fosfomycine via regulating expression of metal-dependent glutathione transferase . It is known that the Klebsiella pneumoniae and P.…”
Section: Introductionmentioning
confidence: 99%